Parent Perspectives of Transition Planning for English Learners with Disabilities - Wu, Yi-Chen; Thurlow, Martha; Johnson, David (Journal of the American Academy of Special Education Professionals, 2024)
The Individuals with Disabilities Education Act emphasizes that students and parents are equal partners in the individualized education program (IEP) process, including planning for transition to postsecondary education, employment, and community living. This is especially important for English learners (ELs) with disabilities, yet little is known about the transition planning meeting experiences of parents of ELs with disabilities. We examined the transition planning experiences of a nationally representative sample of parents of ELs with disabilities and parents of non-ELs with disabilities through an analysis of data from the National Longitudinal Transition Study 2012 (NLTS 2012). Results showed parents of ELs with disabilities were more likely to perceive their children taking a passive role in the IEP transition planning meeting than parents of non-ELs with disabilities. Differences were found in several predictors of parent experiences in IEP transition planning. Recommendations are suggested for transition research and practice for ELs with disabilities.